Acute inflammatory response following lower-and upper-body Wingate anaerobic test in elite gymnasts in relation to iron status - Kochanowicz, A.; Waldzinski, T.; Niespodzinski, B.; Brzezinska, P.; Kochanowicz, M.; Antosiewicz, J.; Mieszkowski, J. (Frontiers in Physiology, 2024)
Introduction Artistic gymnastics is one of the most demanding sports disciplines, with the athletes demonstrating extremely high levels of explosive power and strength. Currently, knowledge of the effect of gymnastic training adaptation on exercise-induced inflammatory response is limited. The study aimed to evaluate inflammatory response following lower- and upper-body high-intensity exercise in relation to the iron status in gymnasts and non-athletes.